Method for improving the activity of low-temperature methanation reaction by establishing a hydrophobic catalytic system

By introducing hydrophobizing materials such as silicon oxide, MFI zeolite molecular sieve, graphite or activated carbon into the methanation catalyst, a hydrophobizing catalytic system is formed, which solves the problems of low low-temperature activity and poor high-temperature stability of existing catalysts, and achieves high conversion rate and long-term stability of the low-temperature methanation reaction.

CN115970746BActive Publication Date: 2025-03-18ZHEJIANG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211659493.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-22
Publication Date
2025-03-18
Estimated Expiration
2042-12-22

AI Technical Summary

Technical Problem

The existing methanation catalysts have low activity under low temperature conditions and poor stability under high temperature conditions, making it difficult to achieve high conversion and long-term stability at low temperatures.

Method used

The hydrophobic catalytic system is used to physically mix the active metal supported by conventional support and the hydrophobic material, or directly use the hydrophobic material as the support to support the active metal to form a catalyst, thereby improving the activity of the methanation reaction and the stability of the catalyst under low temperature conditions.

Benefits of technology

The conversion rate of methanation reaction is greater than 70% under low temperature conditions (less than 300°C), while maintaining the long-term stability of the catalyst and increasing the selectivity of methane by more than 95%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115970746B_ABST
    Figure CN115970746B_ABST
Patent Text Reader

Abstract

The present invention relates to C1 energy molecule conversion technology, and aims to provide a method for improving the activity of low-temperature methanation reaction by establishing a hydrophobic catalytic system. The method comprises: loading an active metal on a conventional carrier, and then mixing it evenly with a hydrophobic material in a physical mixing manner as a catalyst, or directly using a hydrophobic material as a carrier to load the active metal to obtain a catalyst; then the catalyst is used for the methanation reaction of CO or CO2, and the hydrophobic material in the catalyst during the reaction quickly removes the water molecules generated by the reaction to pull the reaction equilibrium forward, thereby improving the activity of the low-temperature methanation reaction and maintaining the long-term stability of the catalyst. The present invention proposes a new implementation method of the hydrophobic catalytic system, which makes the microenvironment of the metal active component relatively dry, and the water molecules generated by the methanation reaction can be quickly removed from the metal active component, accelerating the reaction rate; it can improve the conversion rate and methane selectivity under relatively low temperature conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to C1 energy molecule conversion technology, and in particular to a method for improving the activity of low-temperature methanation reaction by a hydrophobic catalytic system, and specifically to CO / CO2 methanation reaction and catalyst hydrophobicity regulation technology. Background Art

[0002] Methane, with the chemical formula CH4, is composed of one carbon atom and four hydrogen atoms. It is the simplest alkane molecule and is a colorless and odorless gas at room temperature and pressure. It is the main component of natural gas (accounting for about 87%) and is usually used as a fuel or raw material for synthetic chemicals. The methanation process is the core process in coal-to-synthetic natural gas based on the resource characteristics of my country's rich coal, poor oil, and little gas. It is also a hot process for deep removal of CO in fuel cells, especially proton fuel cells, and has important research and application value. This reaction generally refers to the reaction process of hydrogenating carbon monoxide or carbon dioxide to produce methane and water. The reaction formula is:

[0003] CO + 3H2 → CH4 + H2O (1)

[0004] CO2 + 4H2 → CH4 + 2H2O (2)

[0005] The hydrogen in the methanogenesis process usually comes from the electrolysis of water using surplus electricity from renewable energy sources ( Figure 1 ), and at the same time, capture the large amount of carbon dioxide produced in industrial production processes, such as oil refining, cement production, and steel industry, and produce substitute natural gas (SNG) through methanation process, which is directly integrated into the natural gas supply network. With the development of carbon capture and storage infrastructure, carbon dioxide can also be directly captured from the air as a raw material to achieve the production and use of SNG, thereby reducing the use of traditional primary energy sources such as coal and oil. In addition, in some chemical processes or fuel cell systems, methanation reaction can be used to remove trace amounts of carbon monoxide and carbon dioxide in hydrogen to meet the demand for high-quality hydrogen.

[0006] At present, methanation catalysts are mainly oxide-supported catalysts, which are composed of carriers, active components and additives. The carrier usually plays the role of supporting and dispersing the active components, and is usually an oxide, such as silicon oxide (SiO2), aluminum oxide (Al2O3), titanium oxide (TiO2), zinc oxide (ZnO), cerium oxide (CeO2), magnesium oxide (MgO), calcium oxide (CaO), zirconium oxide (ZrO2), etc. The active component plays a major catalytic role in the catalyst, and is usually a precious metal such as rhodium (Rh), platinum (Pt), gold (Au), palladium (Pd) and ruthenium (Ru) or a non-precious metal such as cobalt (Co), iron (Fe) and nickel (Ni). The additive is usually selected from materials that improve the activity of the catalyst and extend the service life of the catalyst, such as alkali metals or rare earth metals. Since the methanation reaction is an exothermic reaction, low temperature is conducive to improving the equilibrium conversion rate of the reaction; however, under low temperature conditions, the catalyst activity is low due to kinetic limitations, so it is necessary to develop an efficient catalyst to achieve an acceptable conversion rate and selectivity. To this end, people have focused their research on optimizing the catalyst itself, such as choosing a suitable preparation method to combine different active components and additives, optimizing the ratio, controlling the loading amount, etc., so as to optimize the metal dispersion and electronic state and improve the catalyst reaction performance.

[0007] However, for current methanation catalysts, when the reaction temperature is lower than 300°C, the conversion rate is usually less than 50%; when the reaction temperature is higher than 300°C, although the conversion rate can reach more than 70%, the catalyst stability is poor; high temperature conditions often lead to sintering and agglomeration of metal active components, and ultimately the conversion rate of the catalyst is greatly reduced in less than 100 hours.

[0008] In view of the fact that the methanation catalysts in the existing technology still have the problems of low activity at low temperatures (<300°C) and poor stability at high temperatures, creating a new catalytic system while achieving a higher conversion rate and maintaining the catalyst's long-term stability is the key to the research. Summary of the invention

[0009] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a method for improving the activity of a low-temperature methanation reaction by using a hydrophobic catalytic system.

[0010] To solve the technical problem, the solution of the present invention is:

[0011] Provided is a catalyst for low-temperature methanation reaction of CO or CO2. The catalyst is obtained by loading active metal on a conventional carrier and then mixing it with a hydrophobic material by physical mixing; or by directly loading the active metal on a hydrophobic material as a carrier; the hydrophobic material is hydrophobically treated silicon oxide (SiO2), MFI zeolite molecular sieve, graphite or activated carbon.

[0012] As a preferred embodiment of the present invention, the hydrophobic treatment refers to a hydrolysis method, a post-modification method or an organic group grafting method.

[0013] As a preferred embodiment of the present invention, the active metal is any one of the following: rhodium (Rh), platinum (Pt), gold (Au), palladium (Pd), ruthenium (Ru), cobalt (Co), iron (Fe) or nickel (Ni); the loading amount of the active metal in the catalyst is 1%-20% by mass.

[0014] As a preferred embodiment of the present invention, the active metal is loaded on a conventional carrier or a hydrophobic material by equal volume impregnation, excess impregnation or co-precipitation.

[0015] As a preferred embodiment of the present invention, the conventional carrier is any one of the following: silicon oxide (SiO2), metal oxide or zeolite molecular sieve.

[0016] As a preferred embodiment of the present invention, the metal oxide is any one of the following: aluminum oxide (Al2O3), titanium oxide (TiO2), zinc oxide (ZnO), cerium oxide (CeO2), magnesium oxide (MgO), calcium oxide (CaO) or zirconium oxide (ZrO2); the zeolite molecular sieve is any one of the following: MFI molecular sieve, ZSM-22 molecular sieve, SAPO-34 molecular sieve, Y molecular sieve, MOR molecular sieve or Beta molecular sieve.

[0017] The present invention also provides a method for improving the activity of low-temperature methanation reaction by establishing a hydrophobic catalytic system, comprising: loading an active metal on a conventional carrier, and then evenly mixing it with a hydrophobic material in a physical mixing manner as a catalyst, or directly using a hydrophobic material as a carrier to load the active metal to obtain a catalyst; then using the catalyst for the methanation reaction of CO or CO2, and during the reaction, the hydrophobic material in the catalyst quickly removes the water molecules generated by the reaction to pull the reaction equilibrium forward, thereby improving the activity of the low-temperature methanation reaction and maintaining the long-term stability of the catalyst.

[0018] As a preferred embodiment of the present invention, the conditions for controlling the methanation reaction are:

[0019] The raw material gas is a mixture of hydrogen and carbon monoxide or a mixture of hydrogen and carbon dioxide, and the molar ratio of H2 / CO or H2 / CO2 is 1 to 4;

[0020] The reaction temperature is controlled in two stages: first, hydrogen is introduced at 450°C and 0.1MPa to reduce the catalyst for 4 hours; then the temperature is lowered to 100-280°C and a mixed gas is introduced, the space velocity is controlled to be 1000-15000mL / h·g, and the pressure is 0.1-3MPa.

[0021] As a preferred embodiment of the present invention, the raw material gas further comprises an inert gas, which is any one of nitrogen (N2), argon (Ar) or helium (He); the mass fraction of the inert gas in the raw material gas is 4-10%.

[0022] Description of the invention principle:

[0023] From the reaction process of carbon monoxide or carbon dioxide hydrogenation to generate methane and water, it can be seen that in addition to generating methane, the methanation reaction also produces a large amount of water. If this water cannot be removed from the reaction system in time, it will cover some metal active sites and affect the subsequent reactions. At the same time, the presence of water will also oxidize some metal active sites, causing deactivation.

[0024] At present, in the process of research and development of catalysts, researchers generally focus on improving the performance of the catalyst itself. Different catalysts, carriers and additives are selected for compatibility and a large number of repetitive experiments are carried out. By controlling the metal loading amount and optimizing the ratio of active components and additives, we try to screen the catalyst that achieves the best balance between catalytic activity and service life. In contrast, the present invention breaks through the inertial way of thinking, starts from the direction of the reaction system, and proposes an innovative solution for the hydrophobic catalytic system. By quickly removing the water molecules generated during the reaction, the reaction equilibrium is pulled forward to move, and the activity of the low-temperature methanation reaction is improved. To this end, the present invention proposes a strategy of physically mixing a carrier loaded with metal active components and a hydrophobic material as a catalyst, or directly loading a metal with a hydrophobic material as a catalyst to accelerate the diffusion of water molecules and greatly improve the reaction activity at the same reaction temperature. In this way, the activity of the low-temperature methanation reaction is improved, while the catalyst stability is maintained for a long time.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The present invention proposes a new method for realizing a hydrophobic catalytic system, in which the catalyst carrier is hydrophobized or physically mixed with hydrophobic materials, so that the microenvironment of the metal active component becomes relatively dry, and the water molecules produced by the methanation reaction can be quickly removed from the vicinity of the metal active component, thereby accelerating the reaction rate.

[0027] 2. In the process of hydrogenating carbon monoxide or carbon dioxide to generate methane and water, the catalyst of the present invention can achieve a conversion rate of more than 70% and a methane selectivity of more than 95% at a reaction temperature of less than 300°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of the methanation reaction process. DETAILED DESCRIPTION

[0029] The implementation of the present invention is described in detail below in conjunction with specific implementation examples.

[0030] Example 1

[0031] 1% Rh / SiO2+hydrophobic MFI molecular sieve catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 100°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 73.7%, and the methane selectivity is 96.8%. The conversion rate remains at ~72% after 100 hours of reaction.

[0032] In the "1% Rh / SiO2+hydrophobic MFI molecular sieve catalyst", 1% refers to the loading amount (mass fraction) of the active metal in the catalyst; "Rh / SiO2" before "+" refers to Rh as the active metal and SiO2 as the conventional carrier; "hydrophobic MFI molecular sieve" after "+" refers to a hydrophobic MFI zeolite molecular sieve, which is physically mixed with the conventional carrier loaded with active metal, and then tableted and sieved to obtain a catalyst product with 40-60 mesh particles. In the following embodiments and comparative examples, similar expressions are interpreted in this way.

[0033] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic MFI molecular sieve is obtained by treating the MFI molecular sieve with an organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0034] Example 2

[0035] 1% Pt / SiO2+hydrophobic MFI molecular sieve catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 150°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 76.5%, and the methane selectivity is 97.9%.

[0036] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic MFI molecular sieve is obtained by treating the MFI molecular sieve with an organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0037] Example 3

[0038] 3% Au / SiO2+hydrophobic MFI molecular sieve catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 150°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and the raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 71.3% and the methane selectivity is 95.2%.

[0039] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic MFI molecular sieve is obtained by treating the MFI molecular sieve with an organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0040] Example 4

[0041] 1% Pd / SiO2+hydrophobic MFI molecular sieve catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 150°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 77.2% and the methane selectivity is 96.4%.

[0042] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic MFI molecular sieve is obtained by treating the MFI molecular sieve with an organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0043] Example 5

[0044] 5% Ru / SiO2+hydrophobic MFI molecular sieve catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 200°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 85.1% and the methane selectivity is 98.5%.

[0045] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic MFI molecular sieve is obtained by treating the MFI molecular sieve with an organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0046] Example 6

[0047] 10% Co / SiO2+hydrophobic MFI molecular sieve catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 6% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 72.9% and the methane selectivity is 95.7%.

[0048] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic MFI molecular sieve is obtained by treating the MFI molecular sieve with an organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0049] Example 7

[0050] 20% Fe / SiO2+hydrophobic MFI molecular sieve catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 280°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 6% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 75.8%, and the methane selectivity is 96.5%.

[0051] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic MFI molecular sieve is obtained by treating the MFI molecular sieve with an organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0052] Example 8

[0053] 15% Ni / SiO2+hydrophobic MFI molecular sieve catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 85.3% and the methane selectivity is 99.1%.

[0054] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic MFI molecular sieve is obtained by treating the MFI molecular sieve with an organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0055] Example 9

[0056] 15% Ni / Al2O3+hydrophobic MFI molecular sieve catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 83.2%, and the methane selectivity is 97.2%.

[0057] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic MFI molecular sieve is obtained by treating the MFI molecular sieve with an organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0058] Example 10

[0059] 20% Ni / TiO2+hydrophobic MFI molecular sieve catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours, and then the temperature was reduced to 280°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 8% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 86.2%, and the methane selectivity is 95.9%.

[0060] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic MFI molecular sieve is obtained by treating the MFI molecular sieve with an organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0061] Embodiment 11

[0062] 10% Ni / ZnO+hydrophobic MFI molecular sieve catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours, and then the temperature was reduced to 280°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 8% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 78.4% and the methane selectivity is 97.3%.

[0063] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic MFI molecular sieve is obtained by treating the MFI molecular sieve with an organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0064] Example 12

[0065] 15% Ni / CeO2+hydrophobic MFI molecular sieve catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours, and then the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 87.2%, and the methane selectivity is 98.5%.

[0066] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic MFI molecular sieve is obtained by treating the MFI molecular sieve with an organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0067] Embodiment 13

[0068] 20% Ni / MgO + hydrophobic MFI molecular sieve catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 85.1% and the methane selectivity is 97.8%.

[0069] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic MFI molecular sieve is obtained by treating the MFI molecular sieve with an organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0070] Embodiment 14

[0071] 20% Ni / CaO+hydrophobic MFI molecular sieve catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 80.4% and the methane selectivity is 95.6%.

[0072] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic MFI molecular sieve is obtained by treating the MFI molecular sieve with an organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0073] Embodiment 15

[0074] 20% Ni / ZrO2+ hydrophobic MFI molecular sieve catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 73.2% and the methane selectivity is 96.4%.

[0075] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic MFI molecular sieve is obtained by treating the MFI molecular sieve with an organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0076] Example 16

[0077] 10% Ni / MFI+hydrophobic graphite catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 280°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 78.3% and the methane selectivity is 98.8%.

[0078] In this embodiment, the active metal is loaded on the conventional carrier by excessive impregnation. The hydrophobic graphite is obtained by treating graphite by a post-modification method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0079] Embodiment 17

[0080] 10% Ni / ZSM-22+hydrophobic graphite catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours, and then the temperature was reduced to 280°C, the reaction pressure was maintained at 0.5 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h-1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 79.4%, and the methane selectivity is 97.5%.

[0081] In this embodiment, the active metal is loaded on the conventional carrier by excessive impregnation. The hydrophobic graphite is obtained by treating graphite by a post-modification method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0082] Embodiment 18

[0083] 10% Ni / SAPO-34+hydrophobic graphite catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours, and then the temperature was reduced to 280°C, the reaction pressure was maintained at 1.0 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 82.3% and the methane selectivity is 96.9%.

[0084] In this embodiment, the active metal is loaded on the conventional carrier by excessive impregnation. The hydrophobic graphite is obtained by treating graphite by a post-modification method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0085] Embodiment 19

[0086] 10% Ni / Y molecular sieve + hydrophobic graphite catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 280°C, the reaction pressure was maintained at 2.0 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 75.6%, and the methane selectivity is 97.7%.

[0087] In this embodiment, the active metal is loaded on the conventional carrier by excessive impregnation. The hydrophobic graphite is obtained by treating graphite by a post-modification method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0088] Embodiment 20

[0089] 10% Ni / MOR molecular sieve + hydrophobic graphite catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 280°C, the reaction pressure was maintained at 3.0 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 79.5%, and the methane selectivity is 96.3%.

[0090] In this embodiment, the active metal is loaded on the conventional carrier by excessive impregnation. The hydrophobic graphite is obtained by treating graphite by a post-modification method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0091] Embodiment 21

[0092] 10% Ni / Beta molecular sieve + hydrophobic graphite catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours, and then the temperature was reduced to 280°C, the reaction pressure was maintained at 3.0 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 86.4% and the methane selectivity is 98.3%.

[0093] In this embodiment, the active metal is loaded on the conventional carrier by excessive impregnation. The hydrophobic graphite is obtained by treating graphite by a post-modification method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0094] Embodiment 22

[0095] 15% Ni / SiO2+hydrophobic activated carbon catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and the raw gas with a molar ratio of H2 / CO of 3 and a volume content of N2 of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 82.9% and the methane selectivity is 99.2%.

[0096] In this embodiment, the active metal is loaded on the conventional carrier by co-precipitation. The hydrophobic activated carbon is obtained by treating graphite by post-modification method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0097] Embodiment 23

[0098] 15% Ni / Al2O3+hydrophobic activated carbon catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of He of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 83.1% and the methane selectivity is 98.4%.

[0099] In this embodiment, the active metal is loaded on the conventional carrier by co-precipitation. The hydrophobic activated carbon is obtained by treating graphite by post-modification method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0100] Embodiment 24

[0101] 15% Ni / CeO2+hydrophobic activated carbon catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and the raw gas with a molar ratio of H2 / CO of 3 and a volume content of N2 of 10% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g-1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 83.6%, and the methane selectivity is 99.2%.

[0102] In this embodiment, the active metal is loaded on the conventional carrier by co-precipitation. The hydrophobic activated carbon is obtained by treating graphite by post-modification method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0103] Embodiment 25

[0104] 20% Ni / TiO2+hydrophobic activated carbon catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and the raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 10% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 81.8%, and the methane selectivity is 98.6%.

[0105] In this embodiment, the active metal is loaded on the conventional carrier by co-precipitation. The hydrophobic activated carbon is obtained by treating graphite by post-modification method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0106] Embodiment 26

[0107] 15% Ni / SiO2+hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 1 and a volume content of N2 of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 81.3%, and the methane selectivity is 95.8%. The conversion rate remains ~80% after 240 hours of stable reaction.

[0108] In this embodiment, the active metal is loaded on the conventional carrier by co-precipitation. The hydrophobic SiO2 is prepared by hydrolysis and mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0109] Embodiment 27

[0110] 15% Ni / Al2O3+hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 2 and a volume content of N2 of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 79.7% and the methane selectivity is 96.6%.

[0111] In this embodiment, the active metal is loaded on the conventional carrier by co-precipitation. The hydrophobic SiO2 is prepared by hydrolysis and mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0112] Embodiment 28

[0113] 15% Ni / CeO2+hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 260°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of N2 of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 82.2% and the methane selectivity is 95.9%.

[0114] In this embodiment, the active metal is loaded on the conventional carrier by co-precipitation. The hydrophobic SiO2 is prepared by hydrolysis and mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0115] Embodiment 29

[0116] 20% Ni / TiO2+hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 260°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 4 and a volume content of N2 of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 83.5%, and the methane selectivity is 97.3%. The conversion rate remains at ~82% after 110 hours of stable reaction.

[0117] In this embodiment, the active metal is loaded on the conventional carrier by co-precipitation. The hydrophobic SiO2 is prepared by hydrolysis and mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0118] Embodiment 30

[0119] The 15% Ni / hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 79.5%, and the methane selectivity is 99.8%.

[0120] In the "15% Ni / hydrophobic SiO2 catalyst", 15% refers to the loading amount (mass fraction) of the active metal in the catalyst, and " / hydrophobic SiO2" means that the active metal is directly loaded on the hydrophobic SiO2 as a carrier; and then the catalyst product with 40-60 mesh particles is obtained by tableting and sieving. In the following embodiments and comparative examples, similar expressions are interpreted in this way.

[0121] In this embodiment, the hydrophobic SiO2 is prepared by a hydrolysis method, and the active metal is loaded by an equal volume impregnation method.

[0122] Embodiment 31

[0123] The 15% Ni / hydrophobic MFI molecular sieve catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 80.6%, and the methane selectivity is 98.3%. The conversion rate remains ~80% after 180 hours of stable reaction.

[0124] In this embodiment, the hydrophobic MFI molecular sieve is obtained by treating the MFI molecular sieve with an organic group grafting method, and the active metal is loaded by an equal volume impregnation method.

[0125] Embodiment 32

[0126] The 15% Ni / hydrophobic graphite catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 78.3% and the methane selectivity is 98.5%.

[0127] In this embodiment, the hydrophobic graphite is obtained by treating graphite with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0128] Embodiment 33

[0129] The 15% Ni / hydrophobic activated carbon catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 77.6%, and the methane selectivity is 98.1%.

[0130] In this embodiment, the hydrophobic activated carbon is obtained by treating the activated carbon by a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0131] Embodiment 34

[0132] 5% Ru / hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 200°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 82.2% and the methane selectivity is 95.3%.

[0133] In this embodiment, the hydrophobic SiO2 is obtained by treating SiO2 with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0134] Embodiment 35

[0135] 5% Ru / hydrophobic MFI molecular sieve catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 200°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 84.1%, and the methane selectivity is 96.7%. The conversion rate remains at ~84% after 120 hours of stable reaction.

[0136] In this embodiment, the hydrophobic MFI molecular sieve is obtained by treating the MFI molecular sieve with an organic group grafting method, and the active metal is loaded by an equal volume impregnation method.

[0137] Embodiment 36

[0138] 5% Ru / hydrophobic graphite catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 200°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 81.5%, and the methane selectivity is 98.3%.

[0139] In this embodiment, the hydrophobic graphite is obtained by treating graphite with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0140] Embodiment 37

[0141] 5% Ru / hydrophobic activated carbon catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 200°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 83.2% and the methane selectivity is 97.5%.

[0142] In this embodiment, the hydrophobic activated carbon is obtained by treating the activated carbon by a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0143] Embodiment 38

[0144] The 10% Co / hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was lowered to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 75.3% and the methane selectivity is 95.4%.

[0145] In this embodiment, the hydrophobic SiO2 is obtained by treating SiO2 with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0146] Embodiment 39

[0147] The 10% Co / hydrophobic MFI molecular sieve catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 78.5%, and the methane selectivity is 97.4%. The conversion rate remains at ~78% after 100 hours of stable reaction.

[0148] In this embodiment, the hydrophobic MFI molecular sieve is obtained by treating the MFI molecular sieve with an organic group grafting method, and the active metal is loaded by an equal volume impregnation method.

[0149] Embodiment 40

[0150] The 10% Co / hydrophobic graphite catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 73.9% and the methane selectivity is 95.7%.

[0151] In this embodiment, the hydrophobic graphite is obtained by treating graphite with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0152] Embodiment 41

[0153] The 10% Co / hydrophobic activated carbon catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 79.3% and the methane selectivity is 95.9%.

[0154] In this embodiment, the hydrophobic activated carbon is obtained by treating the activated carbon by a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0155] Embodiment 42

[0156] 1% Rh / hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 120°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 76.9%, and the methane selectivity is 97.5%. The conversion rate remains at ~76% after 100 hours of reaction.

[0157] In this embodiment, the hydrophobic SiO2 is obtained by treating SiO2 with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0158] Embodiment 43

[0159] 1% Rh / hydrophobic MFI molecular sieve catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours, and then the temperature was reduced to 120°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 81.5%, and the methane selectivity is 95.9%.

[0160] In this embodiment, the hydrophobic MFI molecular sieve is obtained by treating the MFI molecular sieve with an organic group grafting method, and the active metal is loaded by an equal volume impregnation method.

[0161] Embodiment 44

[0162] 1% Rh / hydrophobic graphite catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 120°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 72.8%, and the methane selectivity is 97.1%.

[0163] In this embodiment, the hydrophobic graphite is obtained by treating graphite with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0164] Embodiment 45

[0165] 1% Rh / hydrophobic activated carbon catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 120°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 76.5%, and the methane selectivity is 96.2%.

[0166] In this embodiment, the hydrophobic activated carbon is obtained by treating the activated carbon by a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0167] Embodiment 46

[0168] The 15% Ni / hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 240°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 73.8% and the methane selectivity is 99.9%.

[0169] In this embodiment, the hydrophobic SiO2 is obtained by treating SiO2 with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0170] Embodiment 47

[0171] The 15% Ni / hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 78.5%, and the methane selectivity is 98.9%. The conversion rate remains at ~78% after 200h of reaction.

[0172] In this embodiment, the hydrophobic SiO2 is obtained by treating SiO2 with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0173] Embodiment 48

[0174] The 15% Ni / hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 280°C, the reaction pressure was maintained at 0.5 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 82.6%, and the methane selectivity is 98.5%.

[0175] In this embodiment, the hydrophobic SiO2 is obtained by treating SiO2 with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0176] Embodiment 49

[0177] The 15% Ni / hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 270°C, the reaction pressure was maintained at 0.5 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 83.2% and the methane selectivity is 99.1%.

[0178] In this embodiment, the hydrophobic SiO2 is obtained by treating SiO2 with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0179] Embodiment 50

[0180] The 15% Ni / hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was lowered to 250°C, the reaction pressure was maintained at 1.0 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 80.6%, and the methane selectivity is 99.3%.

[0181] In this embodiment, the hydrophobic SiO2 is obtained by treating SiO2 with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0182] Embodiment 51

[0183] The 15% Ni / hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was lowered to 250°C, the reaction pressure was maintained at 2.0 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 82.4% and the methane selectivity is 98.7%.

[0184] In this embodiment, the hydrophobic SiO2 is obtained by treating SiO2 with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0185] Embodiment 52

[0186] The 15% Ni / hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was lowered to 250°C, the reaction pressure was maintained at 3.0 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 83.7% and the methane selectivity is 99.2%.

[0187] In this embodiment, the hydrophobic SiO2 is obtained by treating SiO2 with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0188] Embodiment 53

[0189] The 15% Ni / hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was lowered to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 1 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 72.5%, and the methane selectivity is 97.6%.

[0190] In this embodiment, the hydrophobic SiO2 is obtained by treating SiO2 with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0191] Embodiment 54

[0192] The 15% Ni / hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was lowered to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 2 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 75.5%, and the methane selectivity is 98.3%.

[0193] In this embodiment, the hydrophobic SiO2 is obtained by treating SiO2 with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0194] Embodiment 55

[0195] The 15% Ni / hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 78.4% and the methane selectivity is 99.0%.

[0196] In this embodiment, the hydrophobic SiO2 is obtained by treating SiO2 with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0197] Embodiment 56

[0198] The 15% Ni / hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was lowered to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 4 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 1000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 86.4% and the methane selectivity is 99.9%.

[0199] In this embodiment, the hydrophobic SiO2 is obtained by treating SiO2 with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0200] Embodiment 57

[0201] The 15% Ni / hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was lowered to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 3000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 83.3% and the methane selectivity is 99.5%.

[0202] In this embodiment, the hydrophobic SiO2 is obtained by treating SiO2 with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0203] Embodiment 58

[0204] The 15% Ni / hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was lowered to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 8000 mL h -1 g -1The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 78.4% and the methane selectivity is 98.7%.

[0205] In this embodiment, the hydrophobic SiO2 is obtained by treating SiO2 with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0206] Embodiment 59

[0207] The 15% Ni / hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was lowered to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 10000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 75.3% and the methane selectivity is 98.1%.

[0208] In this embodiment, the hydrophobic SiO2 is obtained by treating SiO2 with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0209] Embodiment 60

[0210] The 15% Ni / hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 12000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 73.4% and the methane selectivity is 99.3%.

[0211] In this embodiment, the hydrophobic SiO2 is obtained by treating SiO2 with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0212] Embodiment 61

[0213] The 15% Ni / hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was lowered to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 15000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 72.1% and the methane selectivity is 98.2%.

[0214] In this embodiment, the hydrophobic SiO2 is obtained by treating SiO2 with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0215] Embodiment 62

[0216] 15% Ni / SiO2+hydrophobic MFI molecular sieve catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 260°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO2 of 4 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 7200 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO2 conversion rate is 78.7% and the methane selectivity is 99.5%.

[0217] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic MFI molecular sieve is obtained by treating the MFI molecular sieve with an organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0218] Embodiment 63

[0219] 1% Rh / SiO2+hydrophobic MFI molecular sieve catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 150°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO2 of 4 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 7200 mL h -1 g -1The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO2 conversion rate is 73.4%, and the methane selectivity is 98.4%. The conversion rate remains at ~73% after 130 hours of stable reaction.

[0220] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic MFI molecular sieve is obtained by treating the MFI molecular sieve with an organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0221] Embodiment 64

[0222] 20% Ni / TiO2+hydrophobic activated carbon catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 260°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and the raw gas with a molar ratio of H2 / CO2 of 4 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 7200 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO2 conversion rate is 83.3%, and the methane selectivity is 98.8%. The conversion rate remains at ~82% after 110 hours of stable reaction.

[0223] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic activated carbon is obtained by treating the activated carbon by organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0224] Embodiment 65

[0225] 5% Ru / hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 180°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO2 of 4 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 7200 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO2 conversion rate is 76.6%, and the methane selectivity is 96.7%. The conversion rate remains at ~76% after 160 hours of stable reaction.

[0226] In this embodiment, the hydrophobic SiO2 is obtained by treating SiO2 with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0227] Embodiment 66

[0228] The 15% Ni / hydrophobic SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 260°C, the reaction pressure was maintained at 0.5 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO2 of 4 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 7200 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO2 conversion rate is 80.2%, and the methane selectivity is 99.3%. The conversion rate remains ~80% after 800 hours of stable reaction.

[0229] In this embodiment, the hydrophobic SiO2 is obtained by treating SiO2 with a post-modification method, and the active metal is loaded by an equal volume impregnation method.

[0230] Embodiment 67

[0231] 10% Ni / MFI+hydrophobic graphite catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours, and then the temperature was reduced to 260°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO2 of 4 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 7200 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO2 conversion rate is 75.3% and the methane selectivity is 98.3%.

[0232] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic graphite is obtained by treating graphite with an organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0233] Embodiment 68

[0234] 10% Co / hydrophobic graphite catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours, and then the temperature was reduced to 270°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO2 of 4 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 7200 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO2 conversion rate is 73.3% and the methane selectivity is 96.6%.

[0235] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic graphite is obtained by treating graphite with an organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0236] Embodiment 69

[0237] 20% Fe / SiO2+hydrophobic MFI molecular sieve catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 270°C, the reaction pressure was maintained at 0.5 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO2 of 4 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 7200 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO2 conversion rate is 76.2%, and the methane selectivity is 98.7%.

[0238] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic MFI molecular sieve is obtained by treating the MFI molecular sieve with an organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0239] Embodiment 70

[0240] 15% Ni / CeO2+hydrophobic activated carbon catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 260°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and the raw gas with a molar ratio of H2 / CO2 of 1 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 7200 mL h-1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO2 conversion rate is 72.6%, and the methane selectivity is 96.9%.

[0241] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic activated carbon is obtained by treating the activated carbon by organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0242] Embodiment 71

[0243] 15% Ni / CeO2+hydrophobic activated carbon catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 260°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and the raw gas with a molar ratio of H2 / CO2 of 2 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 7200 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO2 conversion rate is 75.4% and the methane selectivity is 97.3%.

[0244] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic activated carbon is obtained by treating the activated carbon by organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0245] Embodiment 72

[0246] 15% Ni / CeO2+hydrophobic activated carbon catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 260°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and the raw gas with a molar ratio of H2 / CO2 of 3 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 7200 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO2 conversion rate is 79.8%, and the methane selectivity is 99.4%.

[0247] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic activated carbon is obtained by treating the activated carbon by organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0248] Embodiment 73

[0249] 15% Ni / CeO2+hydrophobic activated carbon catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 260°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and the raw gas with a molar ratio of H2 / CO2 of 1 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 7200 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO2 conversion rate is 82.2%, and the methane selectivity is 98.7%. The catalyst can stably react for 150 hours and the conversion rate remains at ~81%.

[0250] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic activated carbon is obtained by treating the activated carbon by organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0251] Embodiment 74

[0252] 15% Ni / CeO2+hydrophobic activated carbon catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 260°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and the raw gas with a molar ratio of H2 / CO2 of 1 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO2 conversion rate is 84.2%, and the methane selectivity is 99.3%.

[0253] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic activated carbon is obtained by treating the activated carbon by organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0254] Embodiment 75

[0255] 15% Ni / CeO2+hydrophobic activated carbon catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 260°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and the raw gas with a molar ratio of H2 / CO2 of 1 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 9000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO2 conversion rate is 80.5%, and the methane selectivity is 98.6%.

[0256] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic activated carbon is obtained by treating the activated carbon by organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0257] Embodiment 76

[0258] 15% Ni / CeO2+hydrophobic activated carbon catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 240°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and the raw gas with a molar ratio of H2 / CO2 of 1 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 7200 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO2 conversion rate is 76.2%, and the methane selectivity is 99.8%.

[0259] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic activated carbon is obtained by treating the activated carbon by organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0260] Embodiment 77

[0261] 15% Ni / CeO2+hydrophobic activated carbon catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 280°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and the raw gas with a molar ratio of H2 / CO2 of 1 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 7200 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO2 conversion rate is 84.6%, and the methane selectivity is 99.1%.

[0262] In this embodiment, the active metal is loaded on the conventional carrier by equal volume impregnation. The hydrophobic activated carbon is obtained by treating the activated carbon by organic group grafting method, and is mixed with the conventional carrier loaded with the active metal by mechanical physical grinding.

[0263] Comparative Example 1

[0264] 1% Rh / SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 120°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 4 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 28.6%, and the methane selectivity is 90.3%. After 50 hours of reaction, the conversion rate drops to ~10%.

[0265] In this comparative example, the active metal is loaded on the conventional carrier by equal volume impregnation.

[0266] Comparative Example 2

[0267] The 5% Ru / MFI catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 200°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 4 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 40.5%, and the methane selectivity is 93.7%. After 80 hours of reaction, the conversion rate drops to ~15%.

[0268] In this comparative example, the active metal is loaded on the conventional carrier by equal volume impregnation.

[0269] Comparative Example 3

[0270] The 10% Co / MFI catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 4 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 20.3%, and the methane selectivity is 87.8%. After 60 hours of reaction, the catalyst activity decreases to ~8%.

[0271] In this comparative example, the active metal is loaded on the conventional carrier by equal volume impregnation.

[0272] Comparative Example 4

[0273] The 15% Ni / SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was lowered to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 4 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 35.2%, and the methane selectivity is 97.8%. After 90 hours of reaction, the catalyst activity decreases to ~20%.

[0274] In this comparative example, the active metal is loaded on the conventional carrier by equal volume impregnation.

[0275] Comparative Example 5

[0276] The 20% Ni / TiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 260°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and the raw gas with a molar ratio of H2 / CO of 4 and a volume content of N2 of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 40.6%, and the methane selectivity is 98.3%. After 50 hours of reaction, the catalyst activity decreases to ~25%.

[0277] In this comparative example, the active metal is loaded on the conventional carrier by equal volume impregnation.

[0278] Comparative Example 6

[0279] The 15% Ni / MFI catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was lowered to 250°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO of 4 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 6000 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO conversion rate is 38.9%, and the methane selectivity is 97.5%. After 60 hours of reaction, the catalyst activity decreases to ~28%.

[0280] In this comparative example, the active metal is loaded on the conventional carrier by equal volume impregnation.

[0281] Comparative Example 7

[0282] The 15% Ni / SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 260°C, the reaction pressure was maintained at 0.5 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO2 of 4 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 7200 mL h -1 g -1The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO2 conversion rate is 22.3%, and the methane selectivity is 98.9%. After 100 hours of reaction, the catalyst activity decreases to ~12%.

[0283] In this comparative example, the active metal is loaded on the conventional carrier by equal volume impregnation.

[0284] Comparative Example 8

[0285] The 20% Ni / TiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature dropped to 260°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO2 of 4 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 7200 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO2 conversion rate is 26.8%, and the methane selectivity is 99.5%. After 55 hours of reaction, the catalyst activity decreases to ~14%.

[0286] In this comparative example, the active metal is loaded on the conventional carrier by equal volume impregnation.

[0287] Comparative Example 9

[0288] The 15% Ni / CeO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 260°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO2 of 4 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 7200 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO2 conversion rate is 24.9%, and the methane selectivity is 98.6%. After 45 hours of reaction, the catalyst activity decreases to ~15%.

[0289] In this comparative example, the active metal is loaded on the conventional carrier by equal volume impregnation.

[0290] Comparative Example 10

[0291] 1% Rh / SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 150°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO2 of 4 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 7200 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO2 conversion rate is 20.9%, and the methane selectivity is 96.5%. After 55 hours of reaction, the catalyst activity decreases to ~11%.

[0292] In this comparative example, the active metal is loaded on the conventional carrier by equal volume impregnation.

[0293] Comparative Example 11

[0294] The 5% Ru / SiO2 catalyst was pressed into tablets and sieved into 40-60 mesh particles and loaded into a fixed bed reactor. Hydrogen (20 mL / min) was introduced at 450°C and 0.1 MPa for 4 hours. After that, the temperature was reduced to 180°C, the reaction pressure was maintained at 0.1 MPa, the hydrogen was turned off, and a raw gas with a molar ratio of H2 / CO2 of 4 and a volume content of Ar of 4% was introduced for reaction. The reaction space velocity was 7200 mL h -1 g -1 The reaction tail gas first passes through the gas-liquid separation tank to condense the generated water, and then the gas phase product is analyzed by online chromatography. The obtained CO2 conversion rate is 30.2%, and the methane selectivity is 97.8%. After 70 hours of reaction, the catalyst activity decreases to ~20%.

[0295] In this comparative example, the active metal is loaded on the conventional carrier by equal volume impregnation.

[0296] Summary of main data in embodiments and comparative examples

[0297]

[0298]

[0299]

[0300]

[0301] Data analysis and summary

[0302] We conducted catalyst performance evaluation and stability tests on the comparative examples and some examples under the same conditions. The results showed that the establishment of a hydrophobic catalytic system can generally improve the activity of the CO / CO2 methanation reaction while maintaining a high methane selectivity. In addition, since the hydrophobic system can operate water molecules well, the metal active components can maintain a high performance for a long time, and have better stability than ordinary catalysts.

[0303] From the comparison between Example 1 and Comparative Example 1, it can be seen that after mixing 1% Rh / SiO2 and hydrophobic MFI zeolite, the catalyst activity can be greatly improved at a lower temperature and has a higher selectivity. At the same time, the hydrophobic system catalyst can stably react for 100 hours and the conversion rate remains at ~72%, while the catalyst activity of 1% Rh / SiO2 in Comparative Example 1 decreases to ~10% after reacting for 50 hours at a reaction temperature of 120°C.

[0304] From the comparison between Example 42 and Comparative Example 1, it can be seen that under the same reaction conditions, compared with conventional SiO2, the use of a hydrophobized SiO2 carrier can greatly improve the catalyst activity and has a higher selectivity, while maintaining the high activity of the catalyst for more than 100 hours, while the catalyst activity of 1% Rh / SiO2 in Comparative Example 1 decreases to ~10% after 50 hours of reaction.

[0305] From the comparison between Example 35 and Comparative Example 2, it can be seen that under the same reaction conditions, the conversion rate of 5% Ru / hydrophobic MFI zeolite is more than twice that of 5% Ru / MFI zeolite, and has higher selectivity. At the same time, the 5% Ru / hydrophobic MFI catalyst can stably react for 120 hours and the conversion rate remains at ~84%, while the 5% Ru / MFI zeolite in Comparative Example 2 has a catalyst activity reduced to ~15% after 80 hours of reaction.

[0306] From the comparison between Example 39 and Comparative Example 3, it can be seen that under the same reaction conditions, the conversion rate of 10% Co / hydrophobic MFI zeolite is more than 3 times that of 10% Co / MFI zeolite, and has higher selectivity. At the same time, 10% Co / hydrophobic MFI can stably react for 100 hours and the conversion rate remains at ~78%, while the catalyst activity of 5% Ru / MFI zeolite in Comparative Example 3 decreases to ~8% after 60 hours of reaction.

[0307] From the comparison between Example 47 and Comparative Example 4, it can be seen that under the same reaction conditions, the conversion rate of 15% Ni / hydrophobic SiO2 is increased from 35.2% to 78.5% compared with 15% Ni / SiO2, and a high selectivity is maintained. At the same time, 15% Ni / hydrophobic SiO2 can stably react for 200 hours and the conversion rate remains at ~78%, while the catalyst activity of 15% Ni / SiO2 in Comparative Example 4 decreases to ~20% after 90 hours of reaction.

[0308] From the comparison between Example 29 and Comparative Example 5, it can be seen that under the same reaction conditions, after mixing 20% ​​Ni / TiO2 and hydrophobic SiO2, the catalyst activity is greatly improved compared with the 20% Ni / TiO2 in Comparative Example 5 (from 40.6% to 83.5%), and has considerable selectivity. At the same time, the hydrophobic system catalyst in Example 29 can stably react for 110 hours and the conversion rate remains at ~82%, while the catalyst activity of the 20% Ni / TiO2 in Comparative Example 5 decreases to ~25% after reacting for 50 hours.

[0309] From the comparison between Example 31 and Comparative Example 6, it can be seen that under the same reaction conditions, the conversion rate of 15% Ni / hydrophobic MFI is increased from 38.9% to 80.6% compared with 15% Ni / MFI, and a high selectivity is maintained. At the same time, 15% Ni / hydrophobic MFI can stably react for 180 hours and the conversion rate remains at ~80%, while the catalyst activity of 15% Ni / MFI in Comparative Example 6 decreases to ~28% after 60 hours of reaction.

[0310] From the comparison between Example 66 and Comparative Example 7, it can be seen that under the same reaction conditions, compared with loading 15% Ni on conventional SiO2, loading 15% Ni on a hydrophobized SiO2 carrier can greatly improve the catalyst activity and have higher selectivity, while maintaining the catalyst activity of ~80% for more than 800 hours, while the catalyst activity of 15% Ni / SiO2 in Comparative Example 7 decreases to ~12% after 100 hours of reaction.

[0311] From the comparison between Example 64 and Comparative Example 8, it can be seen that after mixing 20% ​​Ni / TiO2 and hydrophobic activated carbon, the catalyst activity is greatly improved compared with the simple 20% Ni / TiO2 under the same conditions, and has considerable selectivity. At the same time, the hydrophobic system catalyst in Example 64 can stably react for 140 hours and the conversion rate remains at ~82%, while the catalyst activity of 20% Ni / TiO2 in Comparative Example 8 decreases to ~14% after reacting for 55 hours.

[0312] From the comparison between Example 73 and Comparative Example 9, it can be seen that after mixing 15% Ni / CeO2 and hydrophobic activated carbon, the catalyst activity is greatly improved compared with simple 15% Ni / CeO2 under the same conditions, and has considerable selectivity. At the same time, the hydrophobic system catalyst in Example 73 can stably react for 150 hours and the conversion rate remains at ~81%, while the catalyst activity of 15% Ni / CeO2 in Comparative Example 9 decreases to ~15% after reacting for 45 hours.

[0313] From the comparison between Example 63 and Comparative Example 10, it can be seen that after mixing 1% Rh / SiO2 and hydrophobic MFI molecular sieve, the catalyst activity is greatly improved compared with simple 1% Rh / SiO2 under the same conditions, and has considerable selectivity. At the same time, the hydrophobic system catalyst in Example 63 can stably react for 130 hours and the conversion rate remains at ~73%, while the catalyst activity of 1% Rh / SiO2 in Comparative Example 10 decreases to ~11% after reacting for 55 hours.

[0314] From the comparison between Example 65 and Comparative Example 11, it can be seen that under the same reaction conditions, compared with loading 5% Ru on conventional SiO2, loading 5% Ru on a hydrophobized SiO2 carrier can greatly improve the catalyst activity (conversion rate increased from 30.2% to 76.6%), and has considerable selectivity, while maintaining the catalyst activity of ~76% for more than 160 hours, while the catalyst activity of 5% Ru / SiO2 in Comparative Example 11 decreases to ~20% after 70 hours of reaction.

[0315] It can be verified that, compared with the prior art, the present invention proposes a completely new way to realize the hydrophobic catalytic system, thereby improving the activity and stability of the low-temperature methanation reaction.

Claims

1. Application of the catalyst in low-temperature methanation of CO or CO2, characterized in that: The catalyst is obtained by loading active metal on a conventional carrier and then mixing it with a hydrophobic material by physical mixing; or directly loading active metal on a hydrophobic material as a carrier; the hydrophobic material is hydrophobic treated silicon oxide, MFI zeolite molecular sieve, graphite or activated carbon; the hydrophobic treatment refers to hydrolysis, post-modification or organic group grafting; The active metal is any one of the following: rhodium, platinum, gold, palladium, ruthenium, cobalt, iron or nickel; the loading amount of the active metal in the catalyst is 1% to 20% by mass; the active metal is loaded on a conventional carrier or a hydrophobic material by equal volume impregnation, excess impregnation or coprecipitation method; When the catalyst is used, the conditions for controlling the methanation reaction are: the raw gas is a mixed gas of hydrogen and carbon monoxide or a mixed gas of hydrogen and carbon dioxide, and the molar ratio of H2 / CO or H2 / CO2 is 1 to 4; the reaction temperature is controlled in two stages: first, hydrogen is introduced at 450°C and 0.1 MPa to reduce the catalyst for 4 hours; then the temperature is lowered to 100 to 280°C and the mixed gas is introduced instead, and the space velocity is controlled to be 1000 to 15000 mL / h•g and the pressure is 0.1 to 3MPa.

2. The use according to claim 1, characterized in that: The raw material gas further comprises any one of nitrogen, argon or helium, and the mass fraction of nitrogen, argon or helium in the raw material gas is 4-10%.

3. The use according to claim 1, characterized in that: The conventional carrier is any one of the following: silicon oxide, metal oxide or zeolite molecular sieve.

4. The use according to claim 3, characterized in that: The metal oxide is any one of the following: aluminum oxide, titanium oxide, zinc oxide, cerium oxide, magnesium oxide, calcium oxide or zirconium oxide; the zeolite molecular sieve is any one of the following: MFI molecular sieve, ZSM-22 molecular sieve, SAPO-34 molecular sieve, Y molecular sieve, MOR molecular sieve or Beta molecular sieve.

Citation Information

Patent Citations

  • Metal-phase carrier loaded catalyst, and preparation method therefor and uses thereof

    WO2015106634A1